2009
DOI: 10.1093/neuonc/nop022
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of Notch signaling in human gliomas

Abstract: Gliomas are among the most devastating adult tumors for which there is currently no cure. The tumors are derived from brain glial tissue and comprise several diverse tumor forms and grades. Recent reports highlight the importance of cancer-initiating cells in the malignancy of gliomas. These cells have been referred to as brain cancer stem cells (bCSC), as they share similarities to normal neural stem cells in the brain. The Notch signaling pathway is involved in cell fate decisions throughout normal developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 95 publications
3
96
0
3
Order By: Relevance
“…In addition, the expression of some stem cell markers such as CD133, Nestin, BMI-1, MELK, and Notch in GBM tissue has been reported to have prognostic significance in GBM. [167][168][169][170][171][172][173] However, it should be remembered that the stem cell marker expression of tumor cells does not indicate its stem cell potential. Moreover, increasing amounts of evidence have revealed that the therapeutic resistance of glioma stem cells is defined by both the inherent features of glioma stem cells and close interaction with the tumor microenvironment, suggesting that the functional significance of glioma stem cells should be discussed in the context of the tumor microenvironment.…”
Section: Stem Cell Marker Expressionmentioning
confidence: 99%
“…In addition, the expression of some stem cell markers such as CD133, Nestin, BMI-1, MELK, and Notch in GBM tissue has been reported to have prognostic significance in GBM. [167][168][169][170][171][172][173] However, it should be remembered that the stem cell marker expression of tumor cells does not indicate its stem cell potential. Moreover, increasing amounts of evidence have revealed that the therapeutic resistance of glioma stem cells is defined by both the inherent features of glioma stem cells and close interaction with the tumor microenvironment, suggesting that the functional significance of glioma stem cells should be discussed in the context of the tumor microenvironment.…”
Section: Stem Cell Marker Expressionmentioning
confidence: 99%
“…Activation of the Notch pathway through cell-cell interactions initiates a signaling cascade (Pannuti et al, 2010). When a ligand binds to a Notch receptor, the metalloprotease ADAM protein cleaves the extracellular domain of Notch, which initiates intracellular cleavage by the gamma secretase complex (Stockhausen et al, 2010). The gamma-secretase cleavage releases the Notch intracellular domain (NICD), which facilitates its translocation into the nucleus (Miele, 2006).…”
Section: Notch Pathwaymentioning
confidence: 99%
“…So, modulation of these pathways may represent novel therapeutic approach for GBM. Notch is a family of hetero-dimeric transmembrane receptors composed of an extracellular domain responsible for ligand recognition, a transmembrane domain, and an intracellular domain involved in transcriptional regulation (Stockhausen et al, 2010). Notch proteins (and ligands)contain extracellular EGF-like repeats, which interact with the DSL domain of ligands.…”
Section: Trp Channels As Cross-road Of Deregulated Transcriptional Acmentioning
confidence: 99%
“…NICD then translocates into the nucleus and associates with the transcription factor RBP-J. This complex by secruiting other co-activators, stimulates the expression of downstream genes as Cyclin-D1, EGFR, and MAPK (Mitogen-Activated Protein Kinase) inducing cell proliferation, angiogenesis and chemoresistance, in GSCs (Stockhausen et al, 2010). Regarding the role of Notch signaling in GBM, gene microarray analysis have demonstrated that its expression in brain tumors correlated with good versus poor prognosis (Phillips et al, 2006).…”
Section: Trp Channels As Cross-road Of Deregulated Transcriptional Acmentioning
confidence: 99%